Policy for Developing AIDS and Sex Education - แก้วดำเกิง นุชนารถ; เลิศพิริยสุวัฒน์ ชีวนันท์ (Disease Control Journal, 2018)
This study was a qualitative research which aimed to compare AIDS and sex education policy and practice between central and region, to explain pattern and method including related factors of AIDS and sex education in each level. Data was collected from schools under Office of The Basic Education Commission, Ministry of Education by conducting in-depth interview from thirty key informants sampled by region with using semi-structured questionnaire. They consisted of deputy directors, supervisors of supervisor section and officers of promotion education section of Education service Area Office, school principals and teachers teaching AIDS and sex education. It was found that the policy and practices of AIDS and sex education in central and regions were transferred to 185 Education Service Area Offices but they had no clear practical guidelines, lacked continuous monitoring and evaluation, so its implementation in local areas didn’t cover in every level. Pattern and method to teach AIDS and sex education in schools depended on directors of school and their team work. Crucial factors effecting achievement of AIDS and sex education were, 1 concrete policy, 2 curricula appropriated to local context , 3 capacity developing of teacher, 4.monitoring and evaluation, 5 budget support, 6 teaching media/tool and 7 giving information to parents. This study recommended to have concrete AIDS and sex education policy which covers all in-and-out of school youths, capacity building of teachers and their team to have positive attitude to AIDS and sex education and to deliver knowledge to youths effectively, local directions and community to accept teacher, promoting and developing understanding of realize advantage of AIDS and sex education and support continuously its implementation in every level